Co-ordination compounds of inorganic ambidentate ligands - A.I.P. Sinha (1968)
The co-ordination compounds of inorganic ambidentate ligands have been reviewed. The preparation and properties of several cyanate complexes of palladium(II) and platinum(II) of the types [M(NCO)4]2- and [ML2(NCO)2] are described. A criterion for the diagnosis of the mode of linkage of the cyanate group based upon the integrated intensities of absorption of the C–N stretching bands has been developed. The mode of linkage of the cyanate ion in these complexes has been established from the positions of the infrared bands and the intensities of absorption of the C–N stretching bands. The effects of the ligands L on the bonding of the cyanate groups have been discussed in the light of the spectral data. The coordination behaviours of the NCX-(X = O, S or Se)-group of ligands towards palladium(II) and platinum(II) have been compared and a rationale for their differences has been proposed in terms of the charge differences of the N and X atoms. In all these complexes, the cyanate ion has been shown to be N-bonded. [Continues.]